The integration of quality management system in construction industry [electronic resource] - Lydia Nyomek, 1983-; Fakulti Kejuruteraan Awam (2010)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2010